Five green and speckled frogs a count-and-sing book - Burris, Priscilla (New York, NY : Cartwheel Books, 2016)
This count-and-sing book will introduce preschoolers to early math concepts that will engage as well as reinforce their learning.
On board pages.
106093
Keywords: Frogs -- Juvenile fiction; Insects -- Juvenile fiction; Counting; Stories in rhyme -- Juvenile fiction; Nursery rhymes -- Juvenile fiction; Board books. -- Specimens; Board books; Fiction; Juvenile works